Internet for nursing research: a guide to strategies, skills, and resources - Fitzpatrick, Joyce J; Montgomery, Kristen S (Springer Publishing Company, 2004)
This book is a resource for using the internet as a tool in all aspects of nursing research--conducting it, teaching it, and using it. From searching online databases to creating surveys and recruiting research subjects online, the internet opens new possibilities in the research process, as well as new problems. Experienced researchers describe internet-based research methods, information on online methods for teaching research, and accessing the research of others. The appendixes include samples of existing research projects that use internet-based methodologies, as well as a listing of online resources for researchers.